Effects of the COVID-19 pandemic on maternal and perinatal health service utilisation and outcomes in Mozambique: an interrupted time series analysis. Issue 11 (16th November 2022) - Lydon, Megan M; Vilanculos, Joaquim; Martinez, Andres; Barata, Américo; Keyes, Emily
Abstract : Objectives: To measure the effects of the COVID-19 pandemic on maternal and perinatal health services and outcomes in Mozambique. Design: This is an observational study analysing routine service delivery data using interrupted time series analysis. We used 43 months of district-level panel data with April 2020 as the point of interruption, adjusting for seasonality and population growth to analyse service utilisation outcomes. Setting: The 222 public health facilities in Nampula Province, Mozambique, from January 2018 to July 2021. Outcome measures: The change in the number of antenatal care (ANC) visits and facility deliveries, and the change in the rate of adverse birth outcomes at pandemic onset and over time compared with expected levels and trends, respectively. Results: There were no significant disruptions to ANC at pandemic onset. Following this, there was a significant monthly increase of 29.8 (18.2–41.4) first ANC visits and 11.3 (5.5–17.2) ANC visits within the first trimester per district above prepandemic trends. There was no significant change in the number of fourth ANC visits completed. At the onset of COVID-19, districts experienced a significant decrease of 71.1 (−110.5 to −31.7) facility deliveries, but the rate then increased significantly above prepandemic trends. There was no significant increase in any adverse birth outcomes during the pandemic. Conversely, districts observed a significant monthly decrease of 5.3 uterine rupture cases (−9.9 to −0.6) and 19.2 stillbirths (−33.83 to −4.58) per 100 000 facility deliveries below prepandemic trends. There was a significant drop of 23.5 cases of neonatal sepsis/100 000 facility deliveries per district at pandemic onset. Conclusion: Despite pandemic interference, Nampula Province saw no disruptions to ANC, only temporary disruptions to facility deliveries and no increases in adverse birth outcomes. ANC visits surprisingly increased, and the rates of uterine rupture, stillbirth and neonatal sepsis decreased, suggesting that Nampula Province may offer insights about health system resilience.